Did Concentration on Core Competencies Drive Merger and Acquisition Activities in the 1990s? Empirical Evidence for Germany - Katrin Hussinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
In the context of increasing globalization of markets, merger and acquisition activities in the 1990s are said to be driven by reorganization processes with respect to concentration on firms? core competencies in order to increase or maintain market power in international markets. This paper empirically investigates a sample of German domestic mergers in the 1990s to detect the impact of technology and market relatedness on the choice of the merging partner. Results from a conditional logit model show that firms prefer a merging partner within the same industry and with a related technological profile. These findings approve the hypothesis that mergers in the 1990s were undertaken to concentrate on core competencies.
Keywords: C25; O34; O32; G34; 330; M&A; Technological Firm Performance; Market Relatedness; Fusion; Übernahme; Kernkompetenz; Technologie; Schätzung; Deutschland